2019
DOI: 10.1126/sciadv.aax0501
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide adenine dinucleotide as a photocatalyst

Abstract: Nicotinamide adenine dinucleotide (NAD+) is a key redox compound in all living cells responsible for energy transduction, genomic integrity, life-span extension, and neuromodulation. Here, we report a new function of NAD+ as a molecular photocatalyst in addition to the biological roles. Our spectroscopic and electrochemical analyses reveal light absorption and electronic properties of two π-conjugated systems of NAD+. Furthermore, NAD+ exhibits a robust photostability under UV-Vis-NIR irradiation. We demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 45 publications
(56 reference statements)
1
47
0
Order By: Relevance
“…Interestingly, the oxidized form, NAD + , was recently reported to serve as a molecular photocatalyst itself for photocatalytic redox reactions benefiting from the π–π* electronic transition of nicotinamide and adenine in the molecular structure. [ 95 ] The direct photoactivation of oxidoreductases can be achieved using NAD + as photocatalyst, which exhibits systematic simplicity and high efficiency. For completing NADH regeneration and photoenzymatic reaction in an economic and sustainable manner, there are still several challenges to overcome in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the oxidized form, NAD + , was recently reported to serve as a molecular photocatalyst itself for photocatalytic redox reactions benefiting from the π–π* electronic transition of nicotinamide and adenine in the molecular structure. [ 95 ] The direct photoactivation of oxidoreductases can be achieved using NAD + as photocatalyst, which exhibits systematic simplicity and high efficiency. For completing NADH regeneration and photoenzymatic reaction in an economic and sustainable manner, there are still several challenges to overcome in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this system efficiently performs the asymmetric reduction of C=C bonds coupled with biocatalytic water oxidation, and the results compare well with biotransformations performed in whole cells (99 % ee, 80 % yield for N‐methyl maleimide, Scheme , b). Interestingly, it was recently reported that, in addition to its wide‐ranging biological roles, NAD + can act as a photocatalyst and perform new light‐induced redox reactions among which O 2 reduction, H 2 O oxidation and nanoparticles generation through metal reduction …”
Section: Bioinspired Catalysis Using Nad(p)h Redox Cofactorsmentioning
confidence: 99%
“…Interestingly, it was recently reported that, in addition to its wide-ranging biological roles, NAD + can act as a photocatalyst and perform new light-induced redox reactions among which O 2 reduction, H 2 O oxidation and nanoparticles generation through metal reduction. [34] A strategy for the regeneration of synthetic nicotinamide cofactors was devised using two enzymes and a biomimetic nicotinamide analogue, which shuttles between both enzymatic cycles. [35] The first enzyme is an engineered double mutant form of SsGDH, a glucose dehydrogenase from Sulfolobus solfataricus, while the second enzyme is TsER, an enoate reductase from Thermus scotoductus.…”
Section: Bioinspired Catalysis Using Nad(p)h Redox Cofactorsmentioning
confidence: 99%
“… 8 10 Furthermore, combining photocatalysis with biocatalysis offers new possibilities for organic synthesis ranging from new regeneration approaches for cofactor-dependent enzymes, 11 25 photoenzymatic cascades, 26 and “new to nature” reactions catalyzed by photoexcited enzymes. 27 32 Yet, the combination of photocatalysis with biocatalysis is not always unproblematic due to issues of photobleaching 33 and formation of reactive oxygen species. 34 36 …”
Section: Introductionmentioning
confidence: 99%